LIQUID BIOPSY: THERANOSTICS AND PERSONALIZED ONCOLOGY - MALI, AKASH; GOSAVI, SHRAVNI; SHUKLA, GOVIND (Innovare Journal of Sciences, 2020)
Cancer is linked with mutated genes, and the study of tumor-associated genetic alterations is gradually used for diagnostic and treatment purposes. The solid tumors are now obtained from biopsy and/or surgical or biopsy specimens. Tumor cells release circulating free DNA into the blood, but the majority of circulating DNA are often not of cancerous origin, and the detection of cancer-associated alleles in the blood has long been unbearable to achieve. Modern science has overwhelmed these restrictions, making it possible to identify both genetic and epigenetic aberrations. A liquid biopsy (LB) or blood sample can provide the genetic landscape of all cancerous lesions (primary and metastases) as well as offering the opportunity to systematically track genomic evolution. This communication will explore how LB is associated with personalized oncology to predict response to treatments and the development of acquired resistance.